An Analysis of CIRC-FCL Learning Models in Teaching Reading at the University Level - Elsara, Wenny; Masbiran, Gunaldi (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study examines the integration of the Cooperative Integrated Reading and Composition (CIRC) model with Flipped Classroom Learning (FCL) in teaching reading at the university level. The CIRC-b-FCL model combines cooperative learning strategies with student-centered, technology-enhanced approaches to enhance reading comprehension, critical thinking, and engagement. Using a mixed-methods approach, the research evaluates the model's effectiveness in improving reading skills, fostering collaboration, and addressing individual learning needs. Data were collected through surveys, tests, and classroom observations involving university students enrolled in reading courses. Findings revealed a significant improvement in students' reading scores, with an average increase of 82 % for cognitive, 77% for affective and 82 % for attitude. However, This study investigates the effectiveness of the CIRC-b-FCL model in improving students' reading comprehension, critical thinking, and motivation The findings suggest that CIRC-b-FCL can be a valuable approach for improving student learning outcomes in higher education.